Impact of Parental Divorce on Juvenile Delinquency: A Review: Dampak Perceraian Orang Tua terhadap Kenakalan Remaja: Sebuah Tinjauan - Kadhim, Nuha Saeed; Shreef, Noor Salah; Abdulrahem, Duha Majid (Universitas Muhammadiyah Sidoarjo, 2024)
Delinquency among young people has become more prevalent and has affected their families, communities, and quality of life, all of which have contributed significantly to the problem. Parents are essential to a child's growth because they give them the support they need to deal with life's challenges. Parental effectiveness is believed to be a key factor in deciding the results for children of divorced parents, and divorce can have a substantial impact on a child's development. The purpose of this essay is to investigate how serious delinquency in teenagers is impacted by divorce or separation and how parental efficacy may mitigate this impact. Other significant factors contributing to divorce rates, according to Iraqi officials, are early marriages, broader economic challenges, and adultery fostered by modern technologies. In 2021, the 42-million-person nation's courts granted about 73,000 divorces, which is essentially the same number as in 2018. This represents an increase from an average of a little less than 51,700 annually between 2004 and 2014. There were 681 terrorist-related criminals, 601 thieves, and the fewest number of offenders (146) involved in narcotics offenses. With a total of 1453 criminals and a percentage of 64.9%, the 12–14 age group led the crime rate, followed by the 17–15-year-old group with 486 criminals and a rate of 21.7%, and the 9–11-year-old group with 300 criminals and a rate of 13.4%. Highlights: Teen Delinquency & Divorce: Divorce impacts youth delinquency; parental efficacy mitigates effects. Divorce Causes: Early marriage, economy, and technology-driven adultery increase divorce rates. Crime Statistics: Ages 12–14 lead crime rates; theft and terrorism most common. Keywords: Impact, Parental Divorce, Juvenile Delinquency